European Neighborhood Policy as a Cooperation Instrument between Ukraine and the EU - PALAGNYUK, YULIANA (Rocznik Integracji Europejskiej, 2011)
European Neighborhood Policy as a Cooperation Instrument between Ukraine and the EU